Civic Engagement Pada Generasi Z Indonesia - Nur Azizah, Lania; Sari, Liliyana (Jurnal Ilmiah Penelitian Psikologi, 2023)
The Covid-19 pandemic has caused changes in the way individuals engage in the society. This activity change is inseparable from Generation Z’s role as the largest population of productive age in Indonesia. This study aimed to describe civic engagement in Generation Z in Indonesia. A total of 104 research subjects were recruited using a purposive sampling technique in which the criteria was Generation Z aged 15–25 years and able to use the internet. Data were collected by using the Civic Engagement Scale from Doolittle & Faul (2013) (α=.902), adapted to Indonesian, equipped with 11 open-ended questions to explore preferred types of activities, factors influencing the activities, and motivation of civic engagement from the subjects. The results of the data analysis show that 85% of the subjects have a high level of civic engagement which is highly motivated by wanting to help and benefit others. In addition, Generation Z prefers civic engagement activities in person (offline) rather than online. The present study indicates that Generation Z has a high interest and willingness to participate in civic engagement, in which support from the environment plays an important role in this engagement.